HUBUNGAN HAFALAN AL-QUR’AN DENGAN KEDISIPLINAN SISWA KELAS TAHFIZ DI MADRASAH ALIYAH NEGERI 1 BOGOR - Safitri Safitri; Muhammad Dahlan Rabbanie; Tjetjep Suhandi (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
This research aims to find out if there is a memorization relationship of the Qur'an with the discipline of Tahfiz class students in MAN 1 Bogor. This research uses quantitative methods and this type of research is a case study (expost facto) in MAN 1 Bogor. The population was 70 students in Tahfiz class. And the sample determination in this study used the Kerci table so that from 70 Population to 59 students. The data collection methods used are questionnaires, data processing techniques and data analysis which are linear analysis, normality testing and hypothesis testing conducted using regression correlation analysis, data analysis using Correlation statistic Pearson analysis. Test results of the prerequisite test analysis normality of both the Quran and discipline students are in the normal category of the value of sig > 0.05. And the analysis of the second linearity test variables are all linear. The result of the hypothesis test is that the memorization of the Qur'an has a significant relationship with discipline, which is the value of coefficency correlation obtained between the variables of 0.635. Value coefficient of determination obtained value 0.403. This value means that the memorization relationship of the Qur'an with Tahfiz class students ' discipline is 40,3%. While 59.7% of students ' discipline has relationships by other variables that are not researched.